Not Simply a Structural Problem: Psychological Determinants of Headache in Patients with Tumors of the Sellar Region - Siegel, Sonja; Schenk, Thomas; Brabant, Georg; Scholl, Renata Carneiro; Buchfelder, Michael; Kreitschmann-Andermahr, Ilonka (Experimental and Clinical Endocrinology and Diabetes, 2022)
Objective Headache in patients with tumors of the sellar region (TSR) has previously been attributed entirely to biomechanical causes. This study aimed to investigate the influence of psychological determinants for the occurrence of and disability due to headaches in patients with TSR. Methods This was a cross-sectional single-center study with a logistic regression approach. Eighty-four patients (75%) with pituitary adenomas and 28 with other TSR prior to first-time neurosurgery were investigated. One-hundred and twelve patients received standardized questionnaires on personality, headache characteristics, and disability due to headache. Fifty-nine patients additionally filled in questionnaires about coping with stress and pain catastrophizing. Separate logistic regression models were used to predict the risk of headache occurrence and disability due to headache by personality, stress coping, and pain catastrophizing. Results Conscientiousness, neuroticism, and pain catastrophizing were significant predictors of headache occurrence. The amount of explained variance for both models predicting headache occurrence was comparable to that in primary headache. Neuroticism, pain catastrophizing, and humor as a coping strategy predicted disability due to headache with a high variance explanation of 20-40%. Conclusion For the first time, we report data supporting a strong psychological influence on headache and headache-related disability in patients with TSR, which argue against purely mechanistic explanatory models. Physicians treating patients with TSR and headaches should adopt an integrative diagnostic and treatment approach, taking the biopsychosocial model of pain into account.
CRIS-Team WoS Importer:2022-09-02